+0

# Differential equation.....

0
58
3

Solve the following second-order linear ordinary differential equation, with steps please: y''(t) + y(t) = sin(t).
I thank you for any help.

Guest Mar 31, 2017
Sort:

#1
0

Hi the solution is      y = Ae^(-t) - 1/2 sin(t) -1/2 cos(t)

You have the auxiliary equation  k^2(k+1) = 0  where  y = Ae^(kt)     and k cannot be zero. So k= -1 and we have y=Ae^(-t)

Now for the complementary function ,try CF  = a sin(t) + b cos(t).  To find a  and b

substitute in original equation to get

y= Ae^(-t) + asin(t) + b cos(t)           differentiate to get

y' = -Ae^(-t)  +a cos(t)  - b sin(t)         differentiate again   to get

y'' = Ae^(-t)   -a sin(t)+b cos(t)

We want y'' + y'  = sin(t)     so we can equate co-efficients  in sin and cos to get   a= -1/2 and b = -1/2

Guest Mar 31, 2017
#2
0

sorry,slight correction, auxiliary equation is  k(k+1), my typo error.

Guest Mar 31, 2017
#3
0

Solve ( d^2 y(t))/( dt^2) + y(t) = sin(t):
Apply the Laplace transformation ℒ_t[f(t)](s) = integral_0^∞ (f(t))/e^(s t) dt to both sides:
ℒ_t[( d^2 y(t))/( dt^2) + y(t)](s) = ℒ_t[sin(t)](s)

Find the Laplace transformation term by term: :
ℒ_t[( d^2 y(t))/( dt^2)](s) + ℒ_t[y(t)](s) = ℒ_t[sin(t)](s)

Apply ℒ_t[( d^2 y(t))/( dt^2)](s) = s^2 (ℒ_t[y(t)](s)) - s y(0) - y'(0):
ℒ_t[y(t)](s) + -(s y(0)) + s^2 ℒ_t[y(t)](s) - y'(0) = ℒ_t[sin(t)](s)

Apply ℒ_t[sin(t)](s) = 1/(s^2 + 1):
ℒ_t[y(t)](s) + s^2 (ℒ_t[y(t)](s)) - s y(0) - y'(0) = 1/(s^2 + 1)

Simplify:
(s^2 + 1) (ℒ_t[y(t)](s)) - s y(0) - y'(0) = 1/(s^2 + 1)
Solve for ℒ_t[y(t)](s):
ℒ_t[y(t)](s) = (y(0) s^3 + y(0) s + y'(0) + y'(0) s^2 + 1)/(s^2 + 1)^2

Decompose ℒ_t[y(t)](s) via partial fractions:
ℒ_t[y(t)](s) = 1/(s^2 + 1)^2 + (s y(0))/(s^2 + 1) + (y'(0))/(s^2 + 1)
Compute y(t) = ℒ_s^(-1)[1/(s^2 + 1)^2 + (s y(0))/(s^2 + 1) + (y'(0))/(s^2 + 1)](t):

Find the inverse Laplace transformation term by term: :
y(t) = ℒ_s^(-1)[1/(s^2 + 1)^2](t) + ℒ_s^(-1)[(s y(0))/(s^2 + 1)](t) + ℒ_s^(-1)[(y'(0))/(s^2 + 1)](t)

Apply ℒ_s^(-1)[1/(s^2 + 1)^2](t) = 1/2 (sin(t) - t cos(t)):
y(t) = 1/2 (-(t cos(t)) + sin(t)) + ℒ_s^(-1)[(s y(0))/(s^2 + 1)](t) + ℒ_s^(-1)[(y'(0))/(s^2 + 1)](t)

Apply ℒ_s^(-1)[(s y(0))/(s^2 + 1)](t) = y(0) cos(t):
y(t) = 1/2 (-(t cos(t)) + sin(t)) + y(0) cos(t) + ℒ_s^(-1)[(y'(0))/(s^2 + 1)](t)

Apply ℒ_s^(-1)[(y'(0))/(s^2 + 1)](t) = sin(t) y'(0):
y(t) = 1/2 (-(t cos(t)) + sin(t)) + y(0) cos(t) + y'(0) sin(t)

Substitute c_1 = y(0) and c_2 = y'(0):
y(t) = 1/2 (-(t cos(t)) + sin(t)) + c_1 cos(t) + c_2 sin(t)

Simplify the arbitrary constants:
Answer: |y(t) = -1/2 (t cos(t)) + c_1 cos(t) + c_2 sin(t)

Guest Mar 31, 2017

### 8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details